2020
DOI: 10.1186/s12885-020-6714-x
|View full text |Cite
|
Sign up to set email alerts
|

CD8-positive memory T cells in tumor-draining lymph nodes of patients with breast cancer

Abstract: Background: Human immunological memory is a hallmark of the adaptive immune system and plays an important role in the development of effective immune responses against tumors. In the present study, we aimed to determine the frequencies of CD8 + memory T cell subsets including T stem cell memory (TSCM) in tumor-draining lymph nodes of patients with breast cancer (BC). Methods: Mononuclear cells were obtained from axillary lymph nodes of 52 untreated patients with BC and stained for CD8, CCR7, CD45RO, CD95 marke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In this study CD45R0+ cells were found in most of the tumor samples with CD8+ lymphocytes, suggesting that these TILs could be memory CTL (CD8+CD45R0+). In agreement with these results, Vahidi et al (2020) reported an increased frequency of CD8+CD45R0+ lymphocytes associated with large tumor size [49]. Furthermore, it has been reported that CD45R0 and CD8 expression and differentiation in immune cells parallelly increase in patients with BC malignant features such as advanced TS, poorly differentiated tumors and high number of nodes involved, as it was observed in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study CD45R0+ cells were found in most of the tumor samples with CD8+ lymphocytes, suggesting that these TILs could be memory CTL (CD8+CD45R0+). In agreement with these results, Vahidi et al (2020) reported an increased frequency of CD8+CD45R0+ lymphocytes associated with large tumor size [49]. Furthermore, it has been reported that CD45R0 and CD8 expression and differentiation in immune cells parallelly increase in patients with BC malignant features such as advanced TS, poorly differentiated tumors and high number of nodes involved, as it was observed in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it has been reported that CD45R0 and CD8 expression and differentiation in immune cells parallelly increase in patients with BC malignant features such as advanced TS, poorly differentiated tumors and high number of nodes involved, as it was observed in this study. It would suggest that, despite the efforts of the immune system to provide an effective response to eradicate the tumor, it is often functionally impaired as a result of interaction with, or signals from, transformed cells and the tumor microenvironment [49]. These interactions and signals can lead to transcriptional, functional, and phenotypic changes that diminish their ability to eradicate the tumor [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether it is traditional immune cell therapy or new CAR-T cells and T-cell receptor T cells (TCR-T) therapy, all are based on terminally differentiated effector T (T TE ) cells, making it difficult to exert long-lasting anti-tumor effects in the body (8). Adoptive T cell therapy (ACT) is the in vitro expansion and reinfusion of tumorreactive T cells, and is a potential treatment method for the treatment of advanced cancer (9)(10)(11)(12)(13)(14). In infections and cancers, T lymphocytes expand and differentiate into effector cells and memory cells that clear pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rizeq’s study found that activation of the C–C chemokine receptor 7 (CCR7)-related complex increased tumor cell proliferation and migration [ 38 ]. Vahidi’s study concluded that CD8-positive memory T cells in tumor-draining lymph nodes are associated with CCR7 [ 39 ]. We found the specific expression and prognostic value of CCR7 in breast cancer.…”
Section: Discussionmentioning
confidence: 99%